Balance of Payments Manual. (International Monetary Fund, 1993)
The Manual presents concepts, definitions, classifications, and conventions for compilation of balance of payments and international investment position statistics. As the international standard, the Manual serves as a guide for IMF member countries that regularly report balance of payments data to the IMF.